2015
DOI: 10.1111/aogs.12622
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal sonographic evaluation of cervical length in the second trimester of asymptomatic singleton pregnancies, and the risk of preterm delivery

Abstract: The rate of short cervical length of ≤25 mm was lower than expected. The study confirmed the increased risk of spontaneous preterm delivery in women with a short cervix, although the analysis was based on only a few cases. In Sweden, a larger study is needed to evaluate the prevalence of short cervical length and the possible association with preterm delivery before universal screening can be recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
47
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 36 publications
(57 reference statements)
7
47
0
Order By: Relevance
“…The main limitation of this study is the low number of sPTBs ( n = 22), which is explained by our population being a selected low‐risk population. The rate of sPTB before 37 + 0 weeks (4.1%) is consistent with the rates reported in recently published European series of unselected pregnancies and selected low‐risk pregnancies (4.2% and 3.9%, respectively).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The main limitation of this study is the low number of sPTBs ( n = 22), which is explained by our population being a selected low‐risk population. The rate of sPTB before 37 + 0 weeks (4.1%) is consistent with the rates reported in recently published European series of unselected pregnancies and selected low‐risk pregnancies (4.2% and 3.9%, respectively).…”
Section: Discussionsupporting
confidence: 90%
“…To the best of our knowledge, this is the first study to estimate prospectively the ability of mid-trimester CCI to predict sPTB in low-risk women. It was designed specifically to screen a selected low-risk population in which it remains controversial as to whether sonographic CL screening for sPTB works well [10][11][12][21][22][23] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the prevalence of a short cervical length and its sensibility for the detection of spontaneous preterm birth are extremely low [7][8][9] . Consequently, only a small proportion of pregnant women are identified as being at high risk of preterm delivery and potentially benefit from the treatments available [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…comparable to our findings. Furthermore, a Swedish study of 2122 women with CL measurement at 16–23 weeks also reported very low prevalence of CL ≤ 25 mm (0.5%).…”
Section: Discussionmentioning
confidence: 98%